Prevalence of thoracic aortic aneurysms and dilations in patients with intracranial aneurysms - Fordell, Terhi (My University, 2019)
Thoracic aortic aneurysm (TAA) is a disease with a high mortality. If not treated, complications include rupture and dissection of the thoracic aorta. TAA is often asymptomatic and it can be diagnosed incidentally when imaging studies are carried out for other reasons. Estimated prevalence of TAA is 0.16-0.34%. It has been reported that the prevalence of intracranial aneurysms (IA) in patients with TAA is 9 %. The aim of this study was to examine whether the prevalence of thoracic aortic dilatations and aneurysms is higher in patients with ruptured or unruptured IA. This was a retrospective cohort study. Medical records of 519 patients diagnosed with ruptured or unruptured IA at the University Hospital of Turku between 2006 and 2016 were reviewed. Diameters of aorta were measured at three points using reference values by American College of Radiology. Number, shape, diameter and location of IAs were determined. From 519 patients 94.6% had saccular and 5.4% had fusiform IA.41.6% had ruptured and 56.4% unruptured IA. Thoracic aortic dilatation (TAD) was found in 17% and TAA in 6% of patients with saccular IA. 64.2% of the dilatations occurred in the aortic arch. Patients with fusiform IA had a prevalence of 29% for TAD and 18% for TAA. It was found that higher age, rheumatoid disease and excessive alcohol consumption were associated with higher prevalence of TAD and TAA. According to our study the prevalence of TAD and TAA in patients with IA is higher than previous reports of general population state. Our results suggest that the prevalence of TAD and TAA is higher in patients with saccular IA and a history of rheumatoid disease and/or excessive alcohol consumption. Also patients with fusiform IA had a higher prevalence of TAD and TAA.
Keywords: intracranial aneurysm, thoracic aortic aneurysm